Intelligent Emergency Vehicle Preemption Using A Density Based System - Anirudh, Voruganti; Neelaveni Ammal, M; Suryatej, Datla; V Satvik, A (International Journal of Engineering and Technology, 2018)
Transit by road is one of the crude methods of transportation in various parts of the world as of today. The abundance of vehicles utilizing the street is expanding in an ascending order consistently. Because to this reason, trafﬁc congestion in urban areas is becoming inescapable these days. The normal purpose behind trafﬁc blockage is because of poor trafﬁc prioritization, wherein a portion of the paths may have less trafﬁc than the others with measure up to signal light length for both the paths. This Inefﬁcient administration of trafﬁc leads to wastage of crucial time, contamination, wastage of fuel, expenditure of transportation and worry to drivers, and so on however more vitally emergency vehicles like rescue vehicle stall out in trafﬁc. Our project is on density based trafﬁc control with the need to prioritize vehicles like emergency vehicle and ﬁre brigade. In this way, it is especially important to plan a system to keep away from the setbacks. In this way counteracting mishaps, impacts, and trafﬁc jams.
Keywords: Vehicle pre-emption; Image Processing; RaspberryPi; Traffic Density estimation